Quality changes in 12% moisture content canola stored in silo bags under Canadian Prairie conditions. (July 2016) - Chelladurai, V.; Jian, F.; Jayas, D.S.; White, N.D.G.; Manickavasagan, A.; Fields, P.G.
Abstract: A study was conducted for two storage years (2011–12 and 2013–14) to determine the changes in grain quality while storing 12% moisture content (m.c., wet basis) canola seeds in silo bags under Canadian Prairie conditions. Canola seeds were stored in three silo bags (67 tonnes per bag) and unloaded at three different times (one bag at a time) which represent 20 weeks of storage (unloaded in late winter), 28 weeks of storage (unloaded in spring) and 40 weeks of storage (unloaded after summer storage). Canola seed quality parameters (germination, free fatty acid value (FAV), and moisture content), and intergranular composition (CO2 and O2 levels) at different locations in silo bags were analysed every two weeks. Temperature of canola seeds at various locations in the silo bag was recorded every 30 min. The germination of canola seeds at most parts of the silo bags stayed above a safe level up to late winter (20 weeks of storage). At the top layer of the silo bags, germination of canola seeds decreased to below 30% during summer storage (after 40 weeks of storage). Moisture content of canola seeds increased at the top layer in both storage years. The FAV values remained at safe levels until 20 weeks of storage, and increased more than two times the initial values after summer storage. The commercial grades after first, second and third unloading (after 20, 28 and 40 weeks of storage) were Grade 1, Grade 2 and Feed Grade, respectively, in year 1. Whereas for year 2, these were Grade 1, Grade 1 and Grade 2 after first, second and third unloading, respectively. The grain quality analysis and commercial grading results indicated that ambient temperature had a major role in quality of canola during storage. Highlights: Silo bags can be used to store 12% m.c. canola seeds up to the end of winter under Canadian prairie conditions. Ambient temperature plays a major role in safe storage of canola in silo bags. Quality of canola decreased with increase in ambient temperature.